Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/cs500477x
|View full text |Cite
|
Sign up to set email alerts
|

Carbonization of Ethylenediamine Coimpregnated CoMo/Al2O3 Catalysts Sulfided by Organic Sulfiding Agent

Abstract: Co-impregnating binary Cobalt/Molybdenum/Alumina (CoMo/Al 2 O 3 ) catalyst with addition of ethylenediamine was studied for carbonization, sulfidation and hydrodesulfurization using experimental methods. In order to understand the mechanism of carbonization of active phases, theoretical CoMo/Carbon models were produced using density functional theory (DFT) methods. Results from carbonization of the organic component indicate that the formation of support-like carbon species provoke dispersion of active particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…From calculations of the electronic states resulted that carburization energies (ΔE) have exothermic values, as obtained from ET values and its usage on equation 1 (SI-1). These values are also displayed in table 1, where it is possible to determine carburization thermodynamic trend as follows C > CH > CH2 > CH3 > CH3SH, in agreement with observations made by Ge et al [22] and Tuxen et al [23]. When carbon atoms integrate at sulfur edge (as shown in figure 2a) forms a triple bond, meaning sp 2 hybridization by ionic nature to Mo surrounding atoms with similar bond length as for α-MoC phase in agreement with previous reports [24][25]; furthermore the ionic bonding was validated by Mulliken charge analysis as listed in table 2 bending of interface upper part towards carbon zones is observed (figure 2a) and can be highly attributed to electron charge difference before and after carbon was replaced at sulfur edge, as experimentally observed by in-situ operando HRTEM by Ramos et al [19] and previously by Berhault et al [26], as displayed in figure 1b with aid of Synchrotron X-ray diffraction and EELS in order to study carburized process for unsupported molybdenum sulfide catalyst.…”
Section: Carburization Energy and Structural Aspectssupporting
confidence: 89%
“…From calculations of the electronic states resulted that carburization energies (ΔE) have exothermic values, as obtained from ET values and its usage on equation 1 (SI-1). These values are also displayed in table 1, where it is possible to determine carburization thermodynamic trend as follows C > CH > CH2 > CH3 > CH3SH, in agreement with observations made by Ge et al [22] and Tuxen et al [23]. When carbon atoms integrate at sulfur edge (as shown in figure 2a) forms a triple bond, meaning sp 2 hybridization by ionic nature to Mo surrounding atoms with similar bond length as for α-MoC phase in agreement with previous reports [24][25]; furthermore the ionic bonding was validated by Mulliken charge analysis as listed in table 2 bending of interface upper part towards carbon zones is observed (figure 2a) and can be highly attributed to electron charge difference before and after carbon was replaced at sulfur edge, as experimentally observed by in-situ operando HRTEM by Ramos et al [19] and previously by Berhault et al [26], as displayed in figure 1b with aid of Synchrotron X-ray diffraction and EELS in order to study carburized process for unsupported molybdenum sulfide catalyst.…”
Section: Carburization Energy and Structural Aspectssupporting
confidence: 89%
“…Most likely this carbonaceous deposit is present as an adlayer on Al 2 O 3 , which might eventually help in avoiding the direct contact of the active phase with the support and also reduce the possible detrimental interactions between δ/γ‐Al 2 O 3 and the active phase. Now, the active phase on Pdop/δ/γ‐Al 2 O 3 is present on carbon like support leading to a positive impact on the final catalytic activity ,. It is reported in literature that the carbon support or carbon deposited onto the Al 2 O 3 support weaken the interaction between active metals and the support converting type‐I CoMoS phase to more active type‐II CoMoS phase.…”
Section: Resultsmentioning
confidence: 99%
“…Now, the active phase on Pdop/δ/γ‐Al 2 O 3 is present on carbon like support leading to a positive impact on the final catalytic activity ,. It is reported in literature that the carbon support or carbon deposited onto the Al 2 O 3 support weaken the interaction between active metals and the support converting type‐I CoMoS phase to more active type‐II CoMoS phase. Further, Schwartz et.…”
Section: Resultsmentioning
confidence: 99%
“…The increased stacking numbers indicated that the promoters decreased the interaction between Mo and support, facilitating the formation of type II active phase with higher intrinsic activity. 46 Especially, the addition of Ni promoter formed smallest crystallite sizes and highest stacking numbers, which may be one of the reasons for its high catalytic activity. In addition, high-angle annular dark-eld scanning TEM (HADDF-STEM) image (Fig.…”
Section: Catalysts Characterizationmentioning
confidence: 99%